Hubungan Tingkat Stres Terhadap Kadar Gula Darah Pada Klien Diabetes Melitus Tipe 2 Di Wilayah Kerja Puskesmas Jayengan Surakarta - Nindita Prabadewi, Mawar, Okti Sri Purwanti, S.Kep.,M.Kep., Ns.Sp.Kep.M.B, Dian Hudiyawati, S.Kep.,Ns., M.Kep (2016)
Diabetes mellitus was a kind of metabolic diseases with characteristic hyperglycemia that occurs due to abnormalities in insulin secretion, insulin action or both. Diabetes Mellitus disease was a chronic disease that affects the client's psychological the incidence of stress, while stress itself have an impact on an increase in stress hormones epinephrine and cortisol. Hormones epinephrine and cortisol both increase levels of glucose and fatty acids in the blood thereby increasing blood glucose levels. This study aims to determine the relationship of the level of stress on blood glucose levels in type 2 diabetes mellitus clients in the region work of Primary Health Center Jayengan Surakarta. This research was descriptive analytic with cross sectional approach. The study population was all clients of type 2 Diabetes Mellitus in the working area of Primary Health Center Jayengan Surakarta in 2015 which amounted to 2394 clients. The research sample as many as 94 clients Diabetes mellitus obtained by purposive sampling. The research data in the form stress levels and blood glucose levels of clients (fasting blood glucose and Blood Glucose 2 hours post prandial) measured by questionnaires, glucometers and blood glucose stick. The research data analysis used chi square test. The results showed 2 obs value of level of stress with Fasting Blood Glucose (2 obs =15,467 with p-value = 0,000) and level of stress with Blood Glucose 2 hours post prandial (2 obs =19,779 with p-value = 0,000) so the test was H0 decision rejected. Conclusion of research was there was a relationship stress levels with blood glucose levels in type 2 diabetes mellitus client in Primary Health Center Jayengan Surakarta, is the higher the stress client type 2 diabetes, the higher the blood glucose levels or abnormal.